2020
DOI: 10.3390/ijms21062236
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Neurite Outgrowth by Warming Biomaterial Ultrasound Treatment

Abstract: Ultrasound is a method for enhancing neurite outgrowth because of its thermal effect. In order to reach the working temperature to enhance neurite outgrowth, long-time treatment by ultrasound is necessary, while acknowledging that the treatment poses a high risk of damaging nerve cells. To overcome this problem, we developed a method that shortens the ultrasonic treatment time with a warming biomaterial. In this study, we used Fe3O4 nanoparticle-embedded polycaprolactone (PCL) as a sonosensitized biomaterial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Studies have shown that thermal stimulation, as an alternative to neurotrophic factor treatments, has the potential to induce neuronal differentiation of mammalian cells [6,23]. For example, we previously reported the biological effects of a temperature-controlled repeated thermal stimulation (TRTS), a programmed thermal stimulation, on PC12 cells to induce neuritogenesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that thermal stimulation, as an alternative to neurotrophic factor treatments, has the potential to induce neuronal differentiation of mammalian cells [6,23]. For example, we previously reported the biological effects of a temperature-controlled repeated thermal stimulation (TRTS), a programmed thermal stimulation, on PC12 cells to induce neuritogenesis [6].…”
Section: Introductionmentioning
confidence: 99%